Apa yang Melatarbelakangi Keinginan Negara untuk Memiliki Senjata Nuklir? Studi Kasus Iran dan Korea Utara - Muhammad Erza Pradana (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2023)
Why do states want to acquire nuclear weapons? In other words, what drives nuclear-aspiring states? This is the basic question that the author seeks to address in this research. To do so, this research will focus on two standout cases: Iran and North Korea. By employing structural realism as a tool of analysis, the author argues that it is the structure of the international system that drives both Iran and North Korea to acquire nuclear weapons of their own. Specifically, it is the highly unequal distribution of power both regionally and globally that encourages both states to go nuclear. At the global level, both Iran and North Korea found themselves in hostilities with a much more powerful state, the United States. The hostilities and the fact that the United States is way more powerful increase the fear of being attacked in both countries. Similarly, at the regional level, both states face neighbors that are relatively more powerful and have alliances with the United States. Thus, this imbalance of power and the fear it created in both Iran and North Korea give them great incentive to go nuclear, as nuclear weapons would act as a deterrent against any possible aggression. This research is qualitative and based on the literature study data collection method. Keywords: Nuclear proliferation; national security; distribution of capabilities; structural realism REFERENCES Abulof, Uriel. 2014.